Incidência da doença de petri na videira ‘niagara rosada’ no estado de São Paulo - Brasil - Ferreira, Ana Beatriz Monteiro; Leite, Luís Garrigós; Harakava, Ricardo; Padovani, Carlos Roberto [UNESP]; Bueno, César Júnior (FapUNIFESP (SciELO), 2017)
The Petri disease caused mainly by Phaeomoniella chlamydospora and species of Phaeoacremonium is serious, complex, attacks young vine plants and is difficult to be controlled worldwide. In Brazil, São Paulo State is among the largest producers of ‘Niagara Rosada’ grapevine, and there is no official report of this disease in the state. Thus, the aims of the present study were to evaluate the incidence of Petri disease in ‘Niagara Rosada’ grapevine in São Paulo State and to compare methodologies to isolate the causal agents of this disease. Experimental design was completely randomized, testing three culture media (water-agar [WA], potato dextrose agar [PDA] and apple-green bait) with samples of diseased plants, disinfested or not, from nine sampling locality and eight replicates (Petri dish with the media and four fragments of the plants per sample). The number of colonies of causal agents per fragment per dish of each culture medium per locality was determined. Fungal isolates obtained by DNA extraction and sequencing of ITS-5.8S rDNA region [ITS1 TCCGTAGGTGAACCTGCGG and ITS4 TCCTCCGCTTATTGATATGC] and parts of the alpha elongase genes [EF1 ATGGGTAAGGARGACAAGAC and EF2 GGARGTACCAGTSATCATGTT] and beta tubulin genes [Bt2a GGTAACCAAATCGGTGCTGCTTTC and Bt2b ACCCTCAGTGTAGTGACCCTTGGC] were identified. Pathogenicity test was done with one isolate of Phaeomoniella spp. and one isolate of Phaeoacremonium spp. The disease incidence and severity (length of dark streaks in the vascular system) were evaluated. The municipalities Louveira B, Vinhedo, Jundiaí, Jarinu, Porto Feliz, Sao Miguel Arcanjo and Jales were the localities where the causal agents of the disease were present, demonstrating that the Petri disease occurs throughout São Paulo State. The most prevalent species of Phaeoacremonium was P. minimum (= P. aleophilum). Besides P. minimum, the species P. venezuelense was detected only in the municipality of Jales. P. chlamydospora was the only species identified within this genus. Isolation percentage was higher for P. chlamydospora than for Phaeoacremonium spp. The causal agents of the disease must be isolated by removing fragments of the vascular system from the collar region of symptomatic plants, followed by surface disinfection and plating of fragments in PDA culture medium. Incubation in BOD should be at 23ºC for up to 21 days. The apple-green bait method followed by culturing in PDA did not allow isolation of any of the causal agents of the disease. All inoculated plants developed external symptoms and internally the average length of dark streaks was 7.9 cm for P. chlamydospora and 5.2 cm for P. minimum. Control plants remained healthy. Fungi were re-isolated from diseased plants, completing the Koch’s postulates, thus making official the record of Petri disease in ‘Niagara Rosada’ grapevine in São Paulo State, Brazil.
Incidence of petri disease in ‘niagara rosada’ grapevine in São Paulo state - Brazil
Keywords: Decline; Phaeoacremonium aleophilium; Phaeoacremonium minimum; Phaeomoniella chlamydospora